Sex differences in patients’ referral to a headache unit - Varas-Martín, Elena; Ros-González, Isabel; Sierra-Mencía, Álvaro; Recio-García, Andrea; Caballero-Lillo, Paula; González-Osorio, Yésica; Areses-Calderón, Rocío; Sánchez-Rodríguez, Carmen; Peñas-Martínez, M. Luz.; Gonzalez-Martinez, Alicia; Guerrero-Peral, Ángel L. (Frontiers in Neurology, 2026)
BackgroundMigraine is two to three times more prevalent in women than in men, yet sex-related differences in referral patterns and treatment pathways remain insufficiently studied. The objective of the study was to analyze sex distribution upon arrival at a Headache Unit. Secondary objectives included evaluation of age differences, time to first consultation and treatment management.MethodsWe conducted a retrospective observational study based on a prospectively collected registry of patients diagnosed with migraine at the Headache Unit of a tertiary hospital, between January 2008 and January 2025. Variables included demographic data such as sex or age at referral, headache variables including years since migraine onset and previous use of symptomatic or preventive treatment as well as primary care or secondary care referral.ResultsAmong 6,220 patients with migraine 4,956 (79.7%) were female. Female patients were referred at an older age (39.9 vs. 37.1 years; p = 0.004) with longer disease duration (18.1 vs. 14.9 years; p < 0.0001). They were more likely to have received triptans (28.6% vs. 21.5%) and preventive treatment (39.5% vs. 31.8%) prior to referral (p < 0.001 for all). These trends persisted among patients referred from primary care.ConclusionFemale patients were referred to a Headache Unit at an older age and after a longer disease duration, while men were less likely to have received specific migraine treatments such as triptans or preventives. These findings highlight relevant sex-based differences in referral patterns and treatment exposure among patients with migraine.